Narratives unfolding : national art histories in an unfinished world - Langford, Martha (McGill-Queen's/Beaverbrook Canadian Foundation studies in art history., 2017)
"Somewhere between global and local, the nation still lingers as a concept. National art histories continue to be written--some for the first time--while innovative methods and practices redraw the boundaries of these imagined communities. Narratives Unfolding considers the mobility of ideas, transnationalism, and entangled histories in essays that define new ways to see national art in ever-changing nations. Examining works that were designed to reclaim or rethink issues of territory and dispossession, home and exile, contributors to this volume demonstrate that the writing of national art histories is a vital project for intergenerational exchange of knowledge and its visual formations. Essays showcase revealing moments of modern and contemporary art history in Canada, Egypt, Iceland, India, Ireland, Israel/Palestine, Romania, Scotland, Turkey, and the United Arab Emirates, paying particular attention to the agency of institutions such as archives, art galleries, milestone exhibitions, and artist retreats. Old and emergent art cities, including Cairo, Dubai, New York, and Vancouver, are also examined in light of avant-gardism, cosmopolitanism, and migration. Narratives Unfolding is both a survey of current art historical approaches and their connection to the source: art-making and art experience happening somewhere."--